2013
DOI: 10.1097/ta.0b013e31826fc747
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline resuscitation enhances blood pressure recovery and decreases organ injury following hemorrhage in acute alcohol intoxicated rodents

Abstract: Background Acute alcohol intoxication (AAI) impairs the hemodynamic and arginine vasopressin (AVP) counter-regulation to hemorrhagic shock (HS) and lactated Ringer’s (LR) fluid resuscitation (FR). The mechanism of AAI-induced suppression of AVP release in response to HS involves accentuated nitric oxide (NO) inhibitory tone. In contrast, AAI does not prevent AVP response to increased osmolarity produced by hypertonic saline (HTS) infusion. We hypothesized that FR with HTS during AAI would enhance AVP release b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…The impact of AAI on end-organ blood flow has been studied using fluorescent microspheres to determine tissue perfusion 2 hours post-resuscitation (Figure 2). We demonstrated that hemorrhagic shock in AAI animals results in greater reduction of blood flow to the liver, kidney, small and large intestines than that seen in non-intoxicated animals (25). These studies confirmed marked decreases in end-organ blood flow despite fluid resuscitation.…”
Section: Impact Of Acute Alcohol Intoxication On Hemodynamic Counterementioning
confidence: 76%
See 4 more Smart Citations
“…The impact of AAI on end-organ blood flow has been studied using fluorescent microspheres to determine tissue perfusion 2 hours post-resuscitation (Figure 2). We demonstrated that hemorrhagic shock in AAI animals results in greater reduction of blood flow to the liver, kidney, small and large intestines than that seen in non-intoxicated animals (25). These studies confirmed marked decreases in end-organ blood flow despite fluid resuscitation.…”
Section: Impact Of Acute Alcohol Intoxication On Hemodynamic Counterementioning
confidence: 76%
“…The intoxicated trauma patient may be particularly vulnerable to organ injury following traumatic injury and resulting hemorrhage and resuscitation (25). A large proportion of acutely intoxicated trauma victims are also chronic alcohol abusers (26).…”
Section: Impact Of Acute Alcohol Intoxication On Hemodynamic Counterementioning
confidence: 99%
See 3 more Smart Citations